Factors Influencing Laryngeal Vestibular Closure in Healthy Adults. - Abrams, Sophia Werden; Petersen, Courtney; Beall, Jonathan; Namasivayam-MacDonald, Ashwini; Choi, Dahye; Garand, Kendrea L. (Focht) (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Our study aims were (a) to examine laryngeal vestibular closure (LVC) temporal measures in healthy adults across tasks used in the Modified Barium Swallow Impairment Profile (MBSImP) protocol to establish normative reference values and (b) to examine influences of age, gender, and swallow task on LVC temporal measures. Method: A retrospective analysis of 195 healthy adults (85 men, 110 women; age range: 21--89 years) who participated in a videofluoroscopic swallowing study was completed. Seven swallow tasks of standardized viscosities and volumes, as per the MBSImP protocol, were analyzed to measure time-to-LVC and LVC duration (LVCd). Descriptive statistics were employed for all measures of interest. Regression modeling was used to explore relationships between LVC temporal measures (time-to-LVC, LVCd) with age, gender, and swallow task. The relationship between time-to-LVC and LVCd was also explored. Results: Significant findings included an increasing trend in LVCd across age (older individuals had a longer LVCd), with women demonstrating a greater increase. Related to viscosity, LVCd was significantly shorter for pudding compared to thin liquid. Furthermore, when compared to 5-ml tasks, LVCd was significantly longer in cup tasks, while time-to-LVC was significantly shorter. An association was also observed between time-to-LVC and LVCd: As time-to-LVC decreased, LVCd increased. Conclusions: LVCd was influenced by age, gender, and swallow task. Longer time-to-LVC was observed in older individuals, particularly older women, and with thin liquids. Study findings contribute to adult normative reference values for LVC temporal measures (time-to-LVC and LVCd) across MBSImP swallowing tasks.